Graph transformation : 12th International Conference, ICGT 2019, held as part of STAF 2019, Eindhoven, The Netherlands, July 15-16, 2019, Proceedings /: 12th International Conference, ICGT 2019, held as part of STAF 2019, Eindhoven, The Netherlands, July 15-16, 2019, Proceedings. (2019) - Unknown
No abstract available